QOL-26. PLAYFUL SENSORIMOTOR TRAINING TO REDUCE THE SYMPTOMS OF CHEMOTHERAPY-INDUCED PERIPHERAL NEUROPATHY IN PEDIATRIC BRAIN TUMOR PATIENTS- A RANDOMIZED CONTROLLED TRIAL (RESET). Issue 2 (22nd June 2018) - Streckmann, Fiona; Rustler, Vanessa; Tacke, Uta; Hafner, Patricia; Faude, Oliver; Scheinemann, Katrin
Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a highly prevalent and clinically relevant side-effect of cancer treatment. There are no effective treatment options to reduce the symptoms of CIPN. Promising results have so far been achieved with specific exercise interventions. We would therefore like to conduct a prospective, multicenter, randomized two-armed trial. Patients (n=20) will be recruited. Prior to randomization, all primarily eligible patients that have received a platin derivate or vinca-alkaloid, will be screened for symptoms of CIPN. Eligible patients with a neurologically confirmed CIPN will then be randomized either into an intervention group or a control group. Patients in the intervention group will perform a standardized, age-adjusted, specific playful sensorimotor training program twice a week for 12 weeks in addition to usual care, while the control group receives treatment as usual. Data will be assessed at 3 time points: at baseline, after 12 weeks and after 12 weeks of follow-up. Primary endpoint is the Ped-mTNS score in order to subjectively as well as objectively assess the severity of CIPN symptoms. Additional parameters will be assessed via nerve conduction studies, CIPN related pain, dorsiflexion and knee extension as well as postural control. Furthermore, we will be evaluating patients' level of physical activity, walk to run transition time, lower limb power as well as their integration in physical education in school and sport club activities. We hypothesize that patients in the intervention group will be able to reduce relevant symptoms of CIPN, improving related physical functions and enhancing children's social reintegration.